In-situ fabrication of heterostructured SnOx@C/rGO composite with durable cycling life for improved lithium storage. Issue 15 (15th October 2019) - Li, Hui; Zhang, Bao; Ou, Xing; Tang, Linbo; Wang, Chunhui; Cao, Liang; Peng, Chunli; Zhang, Jiafeng
Abstract: Due to their ultra-high theoretical capacity and low discharge potential, rich Sn-based materials are considered promising candidates for lithium ion battery (LIB) anodes; however, the development of SnOx electrodes is restricted by their low conductivity and severe volume change during repeated cycling. In this study, carbon matrix encapsulating heterostructured SnOx ultrafine nanoparticles (SnOx @C/rGO) were synthesized in situ through a facile solvent mixing, followed by thermal calcination. During the decomposition of the Sn-organic precursor, the sizes of the as-prepared SnOx nanoparticles were strictly controlled to 5–10 nm; they were intimately wrapped by the in-situ formation of ultrathin carbon layers, which prevented the agglomeration of nanograins. Furthermore, the SnOx @C nanoparticles were evenly anchored on the surface of reduced graphene oxide (rGO) to construct a highly conductive carbon framework. It is notable that the carbon matrix prepared in situ can accommodate the volumetric change of SnOx and facilitate the transport of Li + ions during continuous cycling. Benefiting from the synergistic effect between the SnOx nanoparticles and carbon matrix prepared in situ, the heterostructured SnOx @C/rGO will confer improved structural stability and reaction kinetics for lithium storage. It delivers a stable reversible discharge capacity of 1092.2 mAh g −1 at a current rate of 0.1 A g −1, and enhanced cycling retention with a capacity of 447.8 mAh g −1 after 1200 cycles at a current rate of 5.0 A g −1 . This strategy provides a rational avenue to design oxide anodes with efficient hierarchical structure for LIB development. Graphical abstract: Image 1